Tanggung Jawab Notaris atas Penyerahan Sertipikat Tanah Tanpa Kata Sepakat para Pihak - Maygi Angga Siswantoro; Sri Astutik; Subekti Subekti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In various business relationships, activities in banking, land, social activities, etc., the need for written evidence in the form of authentic deeds is increasing in line with the growing demand for legal certainty in various economic and social relationships, both at the national, regional and regional levels. and globally. Through an authentic deed that clearly determines rights and obligations, guarantees legal certainty, and at the same time it is hoped that disputes can be avoided. Even though these disputes cannot be avoided, in the process of resolving disputes, authentic deeds which are the strongest and most complete written evidence make a real contribution to resolving cases cheaply and quickly. The objectives to be achieved in the research are:To find out the qualifications of unlawful acts for the actions of a Notary who has handed over a land certificate for the object of sale and purchase without the agreement of the parties. And to find out that the Notary who submitted the Deed of Sale and Purchase without an agreement violated the notary's oath of office.Notaries have an obligation to act in a trustworthy, honest, thorough, independent, impartial manner and safeguard the interests of parties involved in carrying out legal actions. In accordance with the provisions of Article 85 UUJN, the sanctions that can be imposed on a Notary are verbal warning, written warning, temporary dismissal, honorable dismissal, or dishonorable dismissal. Committing other acts which are generally referred to as violations of the Notary's Code of Ethics